2009
DOI: 10.1177/1721727x0900700301
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Respiratory Allergy Treated by Sublingual Immunotherapy

Abstract: The most common allergic diseases, such as rhinitis, asthma and atopic dermatitis, are sustained by allergic inflammation, the treatment of which requires anti-inflammatory activity. Among the available treatments, allergen immunotherapy (IT) has a documented impact on allergic inflammation which persists after its discontinuation and modifies the natural course of allergy. The anti-inflammatory effects of IT, and particularly of sublingual IT (SLIT), are based on the ability to modify the phenotype of T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Psychological therapy is an approach that is being used by adults with cancer to manage a spectrum of treatmentrelated symptoms and facilitate the process of psychological readjustment to the loss, change, and uncertainty characteristic of cancer survivorship (39)(40)(41)(42)(43)(44)(45). With advances in early diagnosis, treatment, and long-term management of cancer, the number of people living with metastatic and advanced cancers has continued to grow worldwide.…”
mentioning
confidence: 99%
“…Psychological therapy is an approach that is being used by adults with cancer to manage a spectrum of treatmentrelated symptoms and facilitate the process of psychological readjustment to the loss, change, and uncertainty characteristic of cancer survivorship (39)(40)(41)(42)(43)(44)(45). With advances in early diagnosis, treatment, and long-term management of cancer, the number of people living with metastatic and advanced cancers has continued to grow worldwide.…”
mentioning
confidence: 99%
“…Possesses potential pleiotropic physiological functions Regulates hematopoiesis and immune response Acts on a broad range of immune and non-immune cells Appears to be an important regulator of Th2 responses Seems to drive airway hypersensitivity and dermatitis Contributes to the pathogenesis of asthma and allergy Plays a role through interaction with TNF-alpha in the pathophysiology of inflammatory bowel disease Does not engage gp 130 Sustains the survival of hematopoietic stem cells Contributes to effects on the cycling and numbers of hematopoietic stem cells Plays a role in the immune responses of the intestine Is involved in the recruitment of Jak l , Jak2, STAT-I, STAT-3, STAT5 signaling pathways, and PI3-kinaselAKT cascade Stimulates inflammatory responses in colon myofibroblasts Activates eosinophil-keratinocyte system Induces the secretion of chemokines CXCL8 (IL-8), CXCLI (growth-related oncogene; GROa), CCL7 (monocyte chemoattractant protein-S; MCP-3), CXCL3, CCLI3, CCLl5) Increases proinflammatory cytokines (IL-6, IL-16 and IL-32), and matrix metalloproteinases (MMP-I, MMP-3, MMP-25 and MMP-7) Shows an additive effect with IL-17A on IL-6, IL-8, secretion In bronchial epithelial cells it elevates gene and protein expressions of epidermal growth factor (EGF), vascular endothelial growth factor (VEGF) and monocyte chemoattractant protein-I (MCP-l/CCL2) In combination with IL-4 or IL-13 enhances VEGF and CCL2 production Contributes to increase the activation of the MAP kinase pathway, ERK and JNK Plays an important role in the induction of autoimmune diseases Induces pruritus and dermatitis in mice Is involved in the proliferation of Band T cells of asthma and allergy (25)(26)(27)(28)(29)(30). Furthermore, a novel subpopulation of memory CD4+ T-lymphocytes was recently identified that produces high levels of IL-17, which plays a major role in the induction of inflammation and tissue destruction in various autoimmune disorders (31)(32).…”
Section: ML Castellani Et Almentioning
confidence: 99%
“…The early cell recruitment within 6 hrs of challenge is likely to be mast cell determined (6)(7), with a potential but undefined contribution from alveolar macrophages as this cell population can generate TNF-alpha and IL-1-beta, inflammatory cells that are of importance to endothelial leukocyte adherence (8). The elaboration of cytokines from T cells contribute to the perpetuation of this response as do chemokine and cytokine generation by airway epithelial cells (9).…”
mentioning
confidence: 99%